Product Development Training on Renewable Energy - Yuliana, Yuliana; Rasidah, Rasidah; Mahrita, Ani; Jonathan, Jonathan; Sidik, Ahmad (Universitas Lambung Mangkurat, 2025)
The energy crisis in Indonesia is becoming increasingly alarming as the population and human activity continue to grow. In addition, there are concerns about environmental pollution and deteriorating human health due to the use of fossil fuels. The development of renewable energy, such as biomass, has great potential to supply sustainable energy in the future. Charcoal briquettes made from biomass waste are a solid fuel that can be used as an alternative solution to energy scarcity at the household level. This activity focused on training students majoring in Renewable Energy Technology at SMKN 1 Palangka Raya to recognize the quality and process high-quality charcoal briquettes, as well as manage the business. The results of this activity were improvements in production and management aspects. After applying technology and innovation during the training, the students' practical results increased to 30 kg per two weeks. Additionally, the students' knowledge and skills in processing charcoal briquettes and conducting business planning improved, from initially having no knowledge to gaining an understanding. The evaluation results stated that the activity had been carried out well, with effective material delivery (90%), adequate facilities (88.57%), alignment with interests (84.29%), and beneficial activities (92.86%).